2002
DOI: 10.1523/jneurosci.22-09-03765.2002
|View full text |Cite
|
Sign up to set email alerts
|

The GABAAReceptor α1Subtype in the Ventral Pallidum Regulates Alcohol-Seeking Behaviors

Abstract: We investigated the potential role of the alpha1-containing GABA(A) receptor in regulating the reinforcing properties of alcohol. To accomplish this, we developed 3-propoxy-beta-carboline hydrochloride (3-PBC), a mixed agonist-antagonist benzodiazepine site ligand with binding selectivity at the alpha1 receptor. We then tested the capacity of 3-PBC to block alcohol-maintained responding in the ventral pallidum (VP), a novel alcohol reward substrate, which primarily expresses the alpha1-receptor isoform. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
115
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 37 publications
6
115
2
Order By: Relevance
“…Rats were trained to lever press for EtOH (10% v/v), using a modified version of the sucrose fading technique June, 2002;Harvey et al, 2002). For all training protocols, animals were water-deprived on the first 3 days of training, using a 23 h fluid deprivation schedule to facilitate lever-pressing.…”
Section: Etoh As the Sole Reinforcermentioning
confidence: 99%
See 4 more Smart Citations
“…Rats were trained to lever press for EtOH (10% v/v), using a modified version of the sucrose fading technique June, 2002;Harvey et al, 2002). For all training protocols, animals were water-deprived on the first 3 days of training, using a 23 h fluid deprivation schedule to facilitate lever-pressing.…”
Section: Etoh As the Sole Reinforcermentioning
confidence: 99%
“…Research on the neuroanatomical basis of alcohol reward has shown that the nucleus accumbens (NACC), ventral tegmental area (VTA), ventral pallidum (VP), central amygdala (CeA), and hippocampus are involved in GABAergic regulation of ethanol (EtOH) reinforcement (Hyytiä and Koob, 1995;Nowak et al, 1998;June et al, 1998aJune et al, , b, 2001Harvey et al, 2002). Opioidergic neurons within the NACC, CeA, and basolateral amygdala (BLA) have also been shown to regulate EtOH reinforcement (Heyser et al, 1999;Hyytiä and Kiianmaa, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations